232. Upaya Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Problem Based Learning Kelas III SDN Pati Lor 05 (psnppg, 2023)
This study aims to improve the learning outcomes of class III students at SDN Pati Lor 05 through the Problem Based Learning model. The research method uses Classroom Action Research which consists of 2 cycles. Data used test and non-test (observation and documentation). The initial data shows that there are many students whose grades have not been completed in KKM. This is because the teacher has not used a learning model that can increase the enthusiasm and enthusiasm of students in participating in learning. The results of the research on the pre-cycle number of students who completed were 3 (38%). Cycle I saw an increase of 62% so that 5 students completed it. Cycle II students' understanding increased so that learning outcomes also increased by 88% or an increase of 2 students completed. This shows that the Problem Based Learning model can improve the learning outcomes of class III students at SDN Pati Lor 05.
Keywords: Learning Outcomes; Problem Based Learning